In Focus/Leadership Philosophies Study Finds a Sea Change in Leadership Approaches - Martin, Andre; Calarco, Allan (Center for Creative Leadership, 2006)
Recently, there has been much discussion about the need for organizations to move from seeing leadership as something carried out by individuals to seeing it as something accomplished collectively.